Bibliometric analysis on exploitation of biogenic gold and silver nanoparticles in breast, ovarian and cervical cancer therapy - Bhandari, Meena; Raj, Seema; Kumar, Ashwani; Kaur, Dilraj Preet (Frontiers in Pharmacology, 2022)
Multifunctional nanoparticles are being formulated to overcome the side effects associated with anticancer drugs as well as conventional drug delivery systems. Cancer therapy has gained the advancement due to various pragmatic approaches with better treatment outcomes. The metal nanostructures such as gold and silver nanoparticles accessible via eco-friendly method provide amazing characteristics in the field of diagnosis and therapy towards cancer diseases. The environmental friendly approach has been proposed as a substitute to minimize the use of hazardous compounds associated in chemical synthesis of nanoparticles. In this attempt, researchers have used various microbes, and plant-based agents as reducing agents. In the last two decades various papers have been published emphasizing the benefits of the eco-friendly approach and advantages over the traditional method in the cancer therapy. Despite of various reports and published research papers, eco-based nanoparticles do not seem to find a way to clinical translation for cancer treatment. Present review enumerates the bibliometric data on biogenic silver and gold nanoparticles from Clarivate Analytics Web of Science (WoS) and Scopus for the duration 2010 to 2022 for cancer treatment with a special emphasis on breast, ovarian and cervical cancer. Furthermore, this review covers the recent advances in this area of research and also highlights the obstacles in the journey of biogenic nanodrug from clinic to market.